The Myth of Beauty and Courage in YOU C-1000 2025 Advertisement - Louis Priscilla Ribka Handoyo (Faculty of Humanities, 2026)
This thesis analyzes a YOU C-1000 advertisement released on January 22, 2025, as the object of the study. This thesis aims to analyze how visual and verbal elements in YOU C-1000 ads are used to construct the beauty and courage myth. This advertisement focuses on Miss Universe 2024, Victoria, and her adventure in Bangka Belitung Beach, promoting YOU C-1000 with the slogan "Healthy Inside, Fresh Outside." This topic is interesting because the advertisement not only promotes a health drink but also conveys the myth of beauty and courage in connection with the ideology of White Supremacy. This paper uses Barthes' Semiotic Theory to analyze all visual and verbal signs from the levels of denotation, connotation, and myth. The data were collected from the YOU C-1000 Instagram and TikTok accounts using a purposive sampling technique, choosing signs, which are in the form of clear images of shots, comprising images with the selected camera angle and distance, as well as verbal audio text with subtitles and reader comments, that are dominant in exposing either the myth of beauty, of courage, or both. Then, the data was processed and identified into two categories: B for beauty, C for courage, and BC for both. Furthermore, all relevant signifiers were analyzed through the stages of denotation, connotation, and myth to dismantle the ideology of White Supremacy within it.
reupload 2026 Rudi H Validasi dan Finalisasi oleh Ratna 15 Juni 2026
Keywords: Beauty; Courage; YOU C-1000; Advertisement